Lukian Prijaced., Les relations entre l’Éthiopie et les nations étrangères. Histoire humaine et diplomatique (des origines à nos jours). Foreign relations with Ethiopia. Human and diplomatic history (from its origins to present) - Brüne, Stefan (Aethiopica, 2017)
Review